Business in the 21st century : a sustainable approach - Berrones-Flemmig, Claudia Nelly; Contreras, Francoise; Dornberger, Utz (Emerald Publishing Limited, 2022)
Business in the 21st Century provides a valuable framework for scholars, managers, leaders and business stakeholders to help navigate the incorporation of SDGs into the business world, shape strategy, improve practices and create a better business future.- Resumé vydavatel
Keywords: podnikatelské projekty; společenská odpovědnost firem; strategický management; udržitelný rozvoj; business planning; corporate social responsibility; strategic planning; sustainable development; elektronické knihy; kolektivní monografie; electronic books; collective monographs